Eksistensi Pendidikan Pesantren dalam Arus Perubahan - Royani, Ahmad (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
Rapid change, demanding the ability of pesantren to respond quickly, precisely, and adaptively.In this paper talks about the existence of pesantren education in the face of the flow of change. This research is focused on the existence conducted by As-Shafii boarding school (pesantren) in the flow of change. The approach used in this study is a case study experienced by remote educational institutions that boarding boarding schools As-syafiI in existence maintain the institution of boarding school. The theory used in this study uses Talcott have four things called AGIL: Adaptation Goal attainment, Integration, Latency. Concluded that the existence of pesantren education in the flow of change as follows; Thefirst adaptation conducted by the boarding school As-SyafiI is to know in detail the existing needs in the community. Second, the development of personality aims to prepare the students and the public to have the knowledge of religion and general science in order to become human beings who are able to practice their knowledge. Third, integrating and integrating school and pesantren systems Thefour patterns of As-SyafiI boarding school institutions are building networking with all components of society, santri guardian, government in building pesantren.Â  ÙØ¯ Ø·ÙØ¨ Ø§ÙØªØºÙØ± Ø§ÙØ³Ø±ÙØ¹ Ø¨ÙØ¯Ø±Ø© Ø§ÙÙØ¯Ø±Ø³Ø©Ø§ÙØ¯Ø§Ø®ÙÙØ© Ø¹ÙÙ Ø§ÙØ§Ø³ØªØ¬Ø§Ø¨Ø© Ø¨Ø³Ø±Ø¹Ø© ÙØ¯ÙØ© ÙØªÙÙÙ. ØªØªØØ¯Ø« ÙØ°Ù Ø§ÙÙØªØ§Ø¨Ø©Ø¹Ù ÙØ¬ÙØ¯ ØªØ¹ÙÙÙ Ø§ÙÙØ¯Ø±Ø³Ø©Ø§ÙØ¯Ø§Ø®ÙÙØ©ÙÙ ÙÙØ§Ø¬ÙØ© ØªØ¯ÙÙ Ø§ÙØªØºÙÙØ±. Ù ÙØ±ÙØ² ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¹ÙÙ ÙØ¬ÙØ¯ ÙØ¯Ø±Ø³Ø© Ø§ÙØ´Ø§ÙØ¹Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ ØªØ¯ÙÙ Ø§ÙØªØºÙÙØ±. ÙØ£ÙØ§ Ø§ÙÙÙÙØ¬ Ø§ÙÙØ³ØªØ®Ø¯Ù ÙÙ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ Ø¯Ø±Ø§Ø³Ø© ØØ§ÙØ© ÙÙ ÙØ¤Ø³Ø³Ø© Ø§ÙØªØ¹ÙÙÙÙØ© Ø§ÙÙØ§Ø¦ÙØ© Ø ÙÙÙ ÙØ¯Ø±Ø³Ø© Ø§ÙØ´Ø§ÙØ¹Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ Ø§ØØªÙØ§Ø¸ ÙØ¬ÙØ¯ÙØ§ÙØ§ÙÙØ¤Ø³Ø³Ø© Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØ¯Ø§Ø®ÙÙØ©. Ù ØªØ³ØªØ®Ø¯Ù ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø©Ø§ÙÙØ¸Ø±ÙØ© Ø§ÙØªÙ ØªÙØ¯ÙØª Ø¨ÙØ§ ØªÙÙÙØª ÙÙØ±Ø³ÙÙÙ ÙÙÙ ÙÙÙÙØ³ØªØ·ÙØ¹ ÙØ¸Ø§Ù Ø§ÙØªÙØ¸ÙÙ Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù Ø£ÙÙØØªÙØ¸ ÙØ¬ÙØ¯ÙÙÙØ¬Ø¨ Ø£Ù ÙÙÙÙ Ø§ÙÙØ¸Ø§Ù ÙÙ Ø£Ø±Ø¨Ø¹Ø© Ø£Ø´ÙØ§Ø¡ ØªØ³ÙÙ(AGIL) Ù ÙÙØ§ÙØªÙÙÙ (adaptation) Ù ØªØÙÙÙ Ø§ÙØ£ÙØ¯Ø§Ù (goalattainment)Ù Ø§ÙØªÙØ§ÙÙ (integration) Ù Ø§ÙØªØ£Ø®Ø± (latency).Ù ÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙØ³ØªØ·ÙØ¹ Ø§ÙØ¨Ø§ØØ« Ø£Ù ÙØ³ØªÙØªØ¬Ø¨Ø£Ù ÙØ¬ÙØ¯ Ø§ÙØªØ±Ø¨ÙØ©ÙÙØ§ÙÙØ¯Ø±Ø³Ø©Ø§ÙØ¯Ø§Ø®ÙÙØ©ÙÙ ØªØ¯ÙÙ Ø§ÙØªØºÙÙØ± ÙÙ Ø¹ÙÙ Ø§ÙÙØÙ Ø§ÙØªØ§ÙÙ : Ø£ÙÙØ§Ø Ø§ÙØªÙÙÙÙ Ø§ÙØ°Ù Ø£Ø¬Ø±ØªÙ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙØ´Ø§ÙØ¹Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ ÙØ¹Ø±ÙØ© Ø§ØØªÙØ§Ø¬Ø§Øª Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØØ§ÙÙØ© Ø¨Ø§ÙØ·Ø±ÙÙØ© Ø§ÙÙØ¨Ø§Ø´Ø±Ø©. Ù Ø«Ø§ÙÙØ§ÙØ ÙÙØ¯Ù ØªØ¯Ø±ÙØ¨ Ø§ÙØ´Ø®ØµÙØ© Ø¥ÙÙ Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙØ·ÙØ§Ø¨ ÙØ§ÙÙØ¬ØªÙØ¹ÙØ£Ù ÙØªÙÙÙ Ø§ÙÙØ¹Ø±ÙØ© Ø§ÙØ¯ÙÙÙØ© ÙØ§ÙÙØ¹Ø±ÙØ© Ø§ÙØ¹Ø§ÙØ© ÙÙÙ ÙØµØ¨ØÙ Ø§ÙÙØ§Ø³ Ø§ÙØ°ÙÙÙÙÙÙØ¯Ø±Ø© Ø¹ÙÙ ÙÙØ§Ø±Ø³Ø© ÙØ¹Ø±ÙØªÙ. Ù Ø«Ø§ÙØ«ÙØ§Ø ÙØ¥Ø¯ÙØ§Ø¬ Ø§ÙØ¹Ø§ÙØ© ÙÙØ¸Ø§ÙØ§ÙÙØ¯Ø±Ø³Ø©Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙØ¥ÙØªØ§Ø¬ Ø£Ø¬ÙØ§Ù ÙÙØ«ÙÙØ©ÙÙ ØÙÙÙÙÙ. Ù Ø±Ø§Ø¨Ø¹ÙØ§Ø Ø§ÙØ£ÙÙØ§Ø· Ø§ÙØªÙ ØªÙÙØ°ÙØ§ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙØ´Ø§ÙØ¹Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ Ø¨ÙØ§Ø¡ Ø§ÙØªÙØ§ØµÙ ÙØ¹ Ø¬ÙÙØ¹ Ø§ÙÙÙÙÙØ§Øª Ù ÙÙ Ø§ÙÙØ¬ØªÙØ¹ ÙØ£ÙÙÙØ§Ø¡ Ø§ÙØ·ÙØ§Ø¨ ÙØ§ÙØÙÙÙØ© ÙØ¨ÙØ§Ø¡ Ø§ÙÙØ¯Ø§Ø±Ø³ Ù ØªÙØ¯ÙÙ. Ø¨Ø§ÙØ¥Ø¶Ø§ÙØ© Ø¥ÙÙ Ø°ÙÙØ ÙØ¥Ù Ø§ÙØ§Ø³ØªØ«ÙØ§Ø± Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù ÙÙØ¨Ø±ÙØ§ÙØ¬ Ø§ÙØ¯Ø§Ø®ÙÙ ÙÙ ÙÙ ÙØ´Ø§Ø·Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙØ´Ø§ÙØ¹Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© Ø§ÙØ°Ù ÙÙØ¯Ù Ø¥ÙÙ Ø®ÙÙ Ø§ÙØ¬ÙÙ Ø§ÙÙØ³ØªÙÙ Ø§ÙÙÙÙØ¯ ÙÙ Ø§ÙØÙØ§Ø© Ø§ÙÙØ¬ØªÙØ¹ÙØ© ÙÙ ÙÙØª ÙØ³ØªÙØ¨Ù.